The physical and optical studies of crystalline silica derived from the green synthesis of coconut husk ash - Anuar, Muhammad Fahmi; Yap, Wing Fen; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Mohamed Khaidir, Rahayu Emilia (MDPI, 2020)
The green synthesis of silica has been extensively explored over the last few decades, as silica compounds found in commercial products can cause negative effects on human health. This calls for alternative ways to produce silica that are safer, cheaper and more environmentally friendly. Some of the agricultural wastes proven to contain silica include rice husk, sugarcane bagasse, coconut shells and coconut husk. This paper describes the synthesis of silica from coconut husk waste, and its physical and optical properties for potential utilization in optical applications. Coconut husk was subjected to fire at 500–700 °C so as to form coconut husk ash (CHA), and was then treated with sulfuric acid to extract silica from the ash. Most of the weight degradation subsequently occurred at temperatures from 221 to 360 °C. X-ray fluorescence (XRF) analysis proved that 91.76% of the silica was obtained, while major peaks on the X-ray diffraction (XRD) spectrum were observed after the acid treatment. Chemical bonds such as Si-O-Si, CH2, -OH and Si-OH were found in the spectrum of the Fourier transform infrared spectroscopy (FTIR). Furthermore, the particles displayed rod-like shapes and irregular sizes, but the particle with sizes ranging from 200–750 nm decreased after the acid treatment. The relationship between the absorption coefficient and photon energy was obtained by finding the optical energy gap, which was found to be 4.3 eV. These data points provide critical information when used in optical applications. The overall studies show that synthesized silica has great potential for use in optical field applications.